Comprehensive risk score of the E-PASS scoring system serves a prognostic indicator for patients after neoadjuvant therapy and curative esophageal cancer surgery: a multicenter retrospective study - Li, Nanjing; Liu, Yixin; Zhou, Jianfeng; Li, Xiang; Lian, Shenglu; Yang, Yushang (Frontiers in Oncology, 2025)
BackgroundNeoadjuvant chemoradiotherapy (nCRT) and curative surgery have been recommended as the standard treatments for locally advanced esophageal cancer. Nevertheless, the postoperative morbidity and long-term survival outcomes for patients following this consensus treatment plan remain suboptimal. Therefore, preoperative risk assessment is essential to identify high-risk patients and predict adverse postoperative outcomes. This multicenter study aimed to evaluate the Estimation of Physiologic Ability and Surgical Stress (E-PASS) scoring system for predicting the short- and long-term outcomes of esophageal cancer patients treated with nCRT and curative esophagectomy.MethodsPatients with esophageal cancer who underwent curative resection between 2010 and 2022 were retrospectively enrolled in this study. The cohort was divided into the low and high comprehensive risk score (CRS) groups. The CRS cutoff value was determined using the Youden index applied to overall survival (OS) curves. Prognostic value was assessed through Cox regression and Kaplan–Meier analyses.ResultsIn total, 814 patients were enrolled, including 556 and 258 patients with low and high CRS, respectively. ROC curve analysis determined that the CRS was a highly specific and sensitive predictive tool for postoperative complication occurrence and severity (AUC=0.889 and 0.838, respectively). When the cutoff value was established using the Youden index applied to overall OS curves, multivariate analysis demonstrated that the CRS was an independent prognostic factor for OS (HR: 1.48; 95% CI 1.14–1.92, P=0.003) and recurrence-free survival (RFS) (HR: 1.44; 95% CI 1.13– 1.82, P=0.002). Furthermore, the Kaplan–Meier survival curves of OS and RFS also demonstrated high CRS group had worse long-term outcomes, irrespective of tumor regression scores and esophageal cancer stage.ConclusionsThe E-PASS scoring system emerges as a visible predictor of short- and long-term outcomes in patients with esophageal cancer undergoing nCRT and curative surgery.